Cancer mortality in Native Americans in North Carolina. - Horner, Ronnie D. (East Carolina University, 1990)
his paper describes age-adjusted mortality from malignant neoplasms for Native Americans in North Carolina for 1968-72 and 1978-82. Sex-specific standardized mortality ratios were calculated from death certificate data, using the cancer mortality experience of White North Carolinians to obtain the number of expected deaths. For most categories and specific sites of cancer, mortality was at or below the expected level, but higher than expected mortality was found for genitourinary cancers in males (SMR=1.62,95%CI=1.15,2.21)forthe1978-82period;withinthis category, there was a higher than expected level of mortality from prostate cancer (SMR = 2.00; 95% CI = 1.36, 2.83) and cancer of the penis and other male genital organs (SMR = 9.09; 95% CI = 1.10, 32.84). Female Native Americans had an elevated mortality from cervical cancer (SMR = 2.27, 95% CI = 1.09, 4.17) for the 1968-72 period only. Originally published American Journal of Public Health, Vol. 80, No. 8, Aug 1990
Keywords: Mortality; Malignant neoplasms; Native Americans; Genitourinary cancers